Tracing potential CBD land uses along roads in historic areas: A study of space syntax using isovist and connectivity attributes along Kayutangan street Malang, Indonesia (International Conference of Graduate School on Sustainability (ICGSS), 2021)
Urban sustainability is an interesting discussion on every development concept in all cities in the world. The issue in urban development that is the focus in several cities is sustainable urban form. Every urban development pays attention to the distribution of land use, which will directly impact the sustainability of the city. One of them is related to an area in the city that has a particular historical value. This study examines the relationship between connectivity and visuals in specific road segments with historical significance. Connectivity is measured using a space syntax approach associated with isovist studies as visual analysis. The study location is along Jalan Kayutangan in Malang, Indonesia, which has a high historical value as a Dutch colonial area. The determination of the isovist study is carried out at specific points along the Kayutangan road, then measured using DepthMapX, a spatial syntax tool to calculate spatial syntactic attributes. The results of this study are expected to assist in determining the best potential for the CBD area along roads that have historical value. It is hoped that this study will help preserve historical buildings and road corridors so that a sustainable city form can be achieved by understanding the potential of spaces along roads that have historical value.